2021
DOI: 10.1101/2021.06.28.21259028
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Enhancing epidemiological investigation of nosocomial SARS-CoV-2 infection with whole genome sequencing: A retrospective cohort study across four hospitals in the UK

Abstract: BackgroundDespite robust efforts, patients and staff acquire SARS-CoV-2 infection in hospitals. In this retrospective cohort study, we investigated whether whole-genome sequencing (WGS) could enhance the epidemiological investigation of healthcare-associated SARS-CoV-2 acquisition.Methods and findingsFrom 17-November-2020 to 5-January-2021, 803 inpatients and 329 staff were diagnosed with SARS-CoV-2 infection across four teaching hospitals in Oxfordshire, UK. We classified cases according to epidemiological de… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…[30][31][32] Of course, protection induced by a safe vaccine is clearly preferable, as the population-wide risk of a serious outcome from an authorized or approved vaccine is expected to be orders of magnitude lower than that from natural infection. Additionally, this study corroborates the findings reported by Lumley et al 33 ; however, the cohort in this study is larger and more generalizable to the general population as it extends beyond health care workers.…”
Section: Discussionsupporting
confidence: 91%
“…[30][31][32] Of course, protection induced by a safe vaccine is clearly preferable, as the population-wide risk of a serious outcome from an authorized or approved vaccine is expected to be orders of magnitude lower than that from natural infection. Additionally, this study corroborates the findings reported by Lumley et al 33 ; however, the cohort in this study is larger and more generalizable to the general population as it extends beyond health care workers.…”
Section: Discussionsupporting
confidence: 91%
“…We 15 Low rates of reinfection have been noted in earlier studies among HCWs, other groups, and the general population. [17][18][19][20][21][22] These studies reported reinfection before 2021 with varying follow-up periods, stages of pandemic, strains of SARS-CoV-2 and its variants, and vaccination use and coverage. In our study, the reinfection risk was highest within the first 180 days and lower thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Future work includes whole-genome sequencing of positive samples from school members and from the community, which might help analyse transmission networks in schools, including during periods of higher incidence, in a manner successfully achieved for SARS-CoV-2 28,29 and a number of health-care-associated pathogens. 30,31 This study included staff and students from secondary schools and colleges of further education but most of the participants were students aged 11-18 years.…”
Section: Discussionmentioning
confidence: 99%